The Effects of Pandemics on the Vulnerability of Food Security in West Africa—A Scoping Review - Liette Vasseur (MDPI AG, 2021)
The purpose of this paper was to show the effects of the Ebola and COVID-19 pandemics on food security vulnerability in West Africa. The methodology is based on a scoping literature review using the PRISMA method. The study showed that food security was affected by the restrictive measures in the different West African countries. In addition, it shows that this region is highly vulnerable to such crises, which can combine their effects with those of other events such as climate change and civil unrest. In both pandemics, all pillars of food security were affected. The effects on urban and rural centers may be very different. The study suggests a better understanding of the differences between rural and urban centers and between men and women and how long-term restraint measures can affect rural areas where agriculture is the main lever for reducing food insecurity. Food security must be seriously considered by governments when implementing restrictive measures during a pandemic. Consideration of health factors alone at the expense of food security can greatly exacerbate health problems and even increase cases of disease.